Examining the causal effects of social exclusion on shame and dissociative detachment - Catton, Ashley K.H.; Yogeeswaran, Kumar; Dorahy, Martin J. (Journal of behavior therapy and experimental psychiatry, 2025)
Dissociative detachment experiences (e.g., derealization, absorption) underpin much psychopathology and are often researched in relation to co-occurring affective states such as shame, the latter being known to occur in situations involving actual or perceived negative social evaluation. The association between shame and dissociative detachment may also be moderated by individual differences in people's need to belong. The goal of the present study was to experimentally investigate the effects of social exclusion on shame and dissociative detachment depending on perceivers' need to belong. After measuring individual differences in need to belong and shame proneness, the Cyberball paradigm was utilized to communicate either social inclusion or exclusion. Following Cyberball, a sample of 281 participants completed measures of state shame and state dissociation. Social exclusion increased dissociative detachment, and these effects were mediated by increases in state shame. These effects were particularly evident among people with a high need to belong. Other individual differences such as rejection sensitivity may also moderate the relationship between exclusion and shame. While Cyberball can be used to investigate shame, it can only induce shame via social exclusion, whereas shame can also be elicited in other ways such as performance failure. Social exclusion can elicit shame, which is most acutely felt by those with a strong need to belong, and this aversive experience appears to be managed by dissociative detachment. •Social exclusion increases shame and dissociative detachment.•Shame mediates effect of social exclusion on dissociative detachment.•Effects of social exclusion on shame and detachment moderated by need to belong.•Mediating role of shame on detachment only among those with high in need to belong.